2010
DOI: 10.1101/gad.1950610
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the miR-143/145 cluster by oncogenic Ras initiates a tumor-promoting feed-forward pathway

Abstract: Although activating mutations in RAS oncogenes are known to result in aberrant signaling through multiple pathways, the role of microRNAs (miRNAs) in the Ras oncogenic program remains poorly characterized. Here we demonstrate that Ras activation leads to repression of the miR-143/145 cluster in cells of human, murine, and zebrafish origin. Loss of miR-143/145 expression is observed frequently in KRAS mutant pancreatic cancers, and restoration of these miRNAs abrogates tumorigenesis. miR-143/145 down-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
270
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(284 citation statements)
references
References 39 publications
13
270
0
1
Order By: Relevance
“…In pancreatic cancer cell lines, the expression of the miR-143/145 cluster is frequently lost. Molecular analysis indicated that RREB1, a transcriptional factor downstream of RAS, can directly bind to the promoter of miR-143/145 and repress their expression [70] . Interestingly, RAS and RREB1 were found to be targets of miR-143 and miR-145, respectively.…”
Section: Mir-34 Familymentioning
confidence: 99%
“…In pancreatic cancer cell lines, the expression of the miR-143/145 cluster is frequently lost. Molecular analysis indicated that RREB1, a transcriptional factor downstream of RAS, can directly bind to the promoter of miR-143/145 and repress their expression [70] . Interestingly, RAS and RREB1 were found to be targets of miR-143 and miR-145, respectively.…”
Section: Mir-34 Familymentioning
confidence: 99%
“…5). miR-143 has been shown to have an antimetastatic effect and is downregulated in several cancers (Takagi et al 2009, Kent et al 2010, Peng et al 2011. miR-143 and miR-145 are often cotranscribed and are usually investigated together as tumour suppressors (Kent et al 2014).…”
Section: :9mentioning
confidence: 99%
“…3 Emerging evidence has shown that miRNAs are involved in cancer initiation and progression. 4 MiR-145 has been reported as an important tumor suppressor gene in ovarian carcinoma, 5,6,7 malignant pleural mesothelioma, 8 breast cancer, 9 pancreatic cancer, 10,11 liposarcoma, 12 colorectal cancer, 13,14,15,16 neuroblastoma, 17 breast cancer, 18,19,20,21 esophageal cancer, 22 bladder cancer, 23,24 urothelial cancer, 25 prostate cancer, 26,27 gastric cancer, 28 and head and neck cancer, 29 and other types. MiR-145 was also implicated in the progression of NSCLC; 30,31,32 however, its exact mechanism is not well established.…”
Section: Introductionmentioning
confidence: 99%